2022
DOI: 10.18480/jjae.24.0_46
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Pathways Linking Agriculture to Child Health: Dietary Diversity and Micronutrient Intake in the Malagasy Highlands

Abstract: Rising micronutrient deficiencies threaten the well-being of preschool-aged children, as is the case for disadvantaged farmers in Madagascar. However, effective interventions to improve their nutritional status are still unknown. This study investigates the disjointed link between agriculture -food/nutrition security and food/nutrition security -nutritional status through a dual approach. Using a panel dataset, our result supports the link between production diversity -dietary diversity, and dietary diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the other hand, Ramahaimandimby et al (2022) asserted that production diversity is associated with are also required. Figure 1 summarizes the above links.…”
Section: Literature Review: Diversification As a Strategy For Nutriti...mentioning
confidence: 99%
“…On the other hand, Ramahaimandimby et al (2022) asserted that production diversity is associated with are also required. Figure 1 summarizes the above links.…”
Section: Literature Review: Diversification As a Strategy For Nutriti...mentioning
confidence: 99%
“…It is also not very clear how agricultural income enhance nutrition. For instance, Ramahaimandimby et al (2022) showed that purchased foods does not appear to increase the overall energy and micronutrient intake. The purchased foods can be sugar, coffee, or cereals, which are not necessarily nutritional, so the link should be further investigated.…”
Section: (R3) Reply By Umetsumentioning
confidence: 99%